2017
DOI: 10.1186/s12936-017-1761-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial landscape in Myanmar: results from a nationally representative survey among community health workers and the private sector outlets in 2015/2016

Abstract: BackgroundIn 2015/2016, an ACTwatch outlet survey was implemented to assess the anti-malarial and malaria testing landscape in Myanmar across four domains (Eastern, Central, Coastal, Western regions). Indicators provide an important benchmark to guide Myanmar’s new National Strategic Plan to eliminate malaria by 2030.MethodsThis was a cross-sectional survey, which employed stratified cluster-random sampling across four regions in Myanmar. A census of community health workers (CHWs) and private outlets with pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…Chloroquine [24]. Our study showed that CCMM under Mitanin programme achieved better availability though there was still scope for improving the availability of ACT further.…”
Section: Discussionmentioning
confidence: 69%
“…Chloroquine [24]. Our study showed that CCMM under Mitanin programme achieved better availability though there was still scope for improving the availability of ACT further.…”
Section: Discussionmentioning
confidence: 69%
“…CHWs have been found to be good in adherence to RD tests [26]. However, most of these studies have made observations in interventions involving a small number of CHWs, newly trained for CCMM [12,24,25]. Our study did not include testing the skills of CHWs because earlier evaluations were available [8,9,23].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study with Mitanin-CHWs in Chhattisgarh state in India in 2015 had described the challenges faced by CHWs in surveillance of malaria that included the availability of diagnostics and drugs [42]. A study in Myanmar found that in the third year after making ACT available in the country 77.7% of the anti-malaria working CHWs had availability of RDT, 83.1% had ACT while 67% had Chloroquine [24]. Our study showed that CCMM under Mitanin programme achieved better availability though there was still scope for improving the availability of ACT further.…”
Section: Discussionmentioning
confidence: 99%
“…Oral artemisinin monotherapy (AMT) was available in 27.7% of private sector outlets. Less than 20% across the private sector could correctly state the national first-line treatment for uncomplicated falciparum and vivax malaria [ 28 ]. The private sector outlets distributed the oral AMT.…”
Section: Discussionmentioning
confidence: 99%